Variances in the effect of caffeine in arabica coffee and robusta towards the aerobic endurance and the heart rate of football players from persatuan sepak bola condong catur FC (PSCC FC) - Ahmad Sujiono; Hardopo Putro, Kukuh; Az Zahra Aulia Ramadhanti; Dhany Diva Pradana; Nadine Nata Safitri; Kisy Jastin Tjeleni; Muhammad Rizqi Eka Putra; Mohamad Althaf YA Ala; Andina Nuary Fitra Nugroho; Shaq Santosa; Dwi Wulansari (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This research seeks to ascertain the variances in the effects of caffeine from Arabica and Robusta coffee on endurance and the heart rate. This research was a descriptive comparative study with 45 samples, utilizing a complete sampling technique followed by random sampling to categorize them into three groups. The data collecting method involved the measurement of the resting heart rate, post-bleep test, recovery, and during the bleep test. An independent sample t-test was employed to examine the differences in VO2max values and heart rates between Arabica and Robusta coffee. The research findings indicate substantial variations in the endurance capabilities of the Arabica and Robusta groups, with a computed t-value of 8.335 exceeding the t-table value of 2.048, and a significance level of 0.000, which is less than 0.05. The disparity in the bleep test results between the Arabica and Robusta groups is at 6.613. The resting pulse rates of the Arabica and Robusta groups show no significant difference, with t values of pulse 0 at -0.277, pulse 1 at -1.248, pulse 2 at -1.430, and pulse 3 at -0.929, compared to a t table value of 2.048. The significance values are 0.784, 0.223, 0.164, and 0.361. 0.05 The recovery pulse rate of the Arabica and Robusta groups show no significant difference, with a t count of -0.929 (t table 2.048) and a significance value of 0.361. 0.05 The disparity in the bleep test results between the Arabica and Robusta groups is at 2.933. The recovery pulse of the Arabica and Robusta groups show no significant difference, with a t value of 1.910 for pulse 5 and 0.624 for pulse 6, compared to a t table value of 2.048. Has a significance value of 0.066, 0.538 > 0.05. Arabica coffee enhances endurance more markedly than Robusta coffee. Robusta coffee can elevate resting heart rate and heart rate following a bleep test. Robusta coffee might also expedite the recovery pulse more than Arabica coffee.